Класифікація та оцінка умов ущільненої забудови - Григоровський, П. Є.; Надточій, М. І. (Ways to Improve Construction Efficiency, 2012)
The paper presents a classification of conditions compacted construction, indicators that characterize the intensity of the impact of each of the conditions.